Risk for Additional Infarction in Emergency Carotid Artery Endarterectomy in Thrombectomy Acute Stroke Patients. (August 2022) - Yousefian Jazi, Ehsan; Wiesmann, Martin; Reich, Arno; Gombert, Alex; Pinho, João; Kotelis, Drosos; Nikoubashman, Omid
Purpose: Thromboembolic occlusion of the middle cerebral artery with tandem occlusion of the internal carotid artery is a life-threatening condition with unfavorable neurological outcome. We perform emergency carotid endarterectomy in the same anesthesia session as thrombectomy in our angiography suite whenever needed despite the absence of electrophysiological neuromonitoring.Methods: We evaluated 47 thrombectomy patients with emergency CEA in our clinic between June 2013 and November 2020. To determine whether there were additional infarctions due to the surgical procedure, we assessed the initial diagnostic CT imaging for previously infarcted areas, cerebral perfusion, and vascular anatomy, including collateralization in the Circle of Willis (CoW). We then analyzed follow-up imaging with respect to new infarctions that could not be explained by the initial stroke.Results: 5 of 47 (11%) patients had a complete CoW. There was contralateral internal carotid artery (ICA) stenosis or occlusion in 18/47 (38%) patients. Surgical procedure was eversion CEA in 34 (72%) and with a patch graft CEA in 13 (28%) cases. Shunts were used during surgery in 17/47 (36%) patients. Two patients suffered from an additional infarction in a new territory, however this was not caused by the surgical procedure but due to embolism during endovascular thrombectomy. In 1 of these 2 patients a hemodynamic border zone infarction was also observed, which could have developed during thrombectomy as well as during surgery, although this could not be attributed with absolute certainty to the surgery. The final infarction size was significantly larger in patients with contralateral ICA stenosis or occlusion ( P = .038). Neither CoW anatomy nor the absence of a shunt during surgery could be identified as risk factors for additional infarction.Conclusion: Emergency surgery in the angiography suite without neuromonitoring was not associated with an increased additional stroke rate in our patient cohort.